Enhancing students’ nature of science understanding through project-based learning and mind mapping - Sri Sukaesih; Siti Zubaidah; Susriyati Mahanal; Dwi Listyorini (International Journal of Evaluation and Research in Education (IJERE), 2022)
This study aimed to investigate students' understanding of the nature of science (NOS) in project-based learning combined with mind mapping (PjBL-MM), students' NOS understanding across gender, and PjBL-MM and gender interaction's effect on students' NOS understanding of conservation education. It employed a pretest-post-test non-equivalent group design. The research population consisted of first-year students at the Biology Department, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang, Central Java, Indonesia. Thus, the study consisted of 98 students (40 males and 58 females) selected randomly from three different classes. The students' NOS understanding was assessed using the views of NOS type B questionnaire. The learning models' effectiveness was tested using ANCOVA. The results showed a significant difference in students' NOS understanding, PjBL-MM group reported the highest NOS score among all treatment groups in the Conservation education course. There is a significant difference NOS understanding between male and female students. Females outperformed males in NOS understanding. However, PjBL-MM and gender interaction did not affect students' NOS understanding. This study is expected to encourage the implementation of PjBL-MM to improve the students' NOS understanding. The educators are also expected to empower NOS understanding through students' active participation in science by implementing project-based learning combined with mind mapping techniques.